Environmental education: educational tendencies, epistemological sources and the project pedagogy - Terossi, Marcos Jose [UNESP]; Santana, Luiz Carlos [UNESP] (Univ Metodista Piracicaba-unimep, 2015)
Considering education as a human activity, political and social will undertake in this article reflects on pedagogical tendencies that historically were most frequent in school education in Brazil, its main epistemological sources, as well as emerging tendencies in these Environmental Education. From this framework and a critical, transformative and emancipatory Environmental Education, reflect on the Pedagogy of Projects as an educational practice, considering its possibilities and limits.
Keywords: ENVIRONMENTAL EDUCATION; PEDAGOGY; METHOD; PROJECTS